Advancing holistic development in college student athletes: Probing prosocial behavior, gratitude, and the satisfaction of basic psychological needs - Haidong Liu; Mohamad Ibrani Shahrimin Bin Adam Assim; Azhar Bin Yaacob; Tengku Fadilah Tengku Kamalden; Mohd Rozilee Wazir Bin Norjali Wazir (EnPress Publisher, LLC, 2024)
: Interconnected components of holistic development, such as being thankful, addressing basic psychological needs, and acting effectively toward others, should be a priority for college athletes. Athletes at the College level need all-encompassing support systems to ensure their health, happiness, and success because of the special difficulties they have juggling their academic, athletic, and personal schedules. Problems with work-life balance, stress, and performance expectations all impede College Student Athletes’ holistic development. A thorough plan that considers all of the social, emotional, and psychological aspects impacting athlete development is necessary to overcome these obstacles. An Integrated Holistic Development Program for College Athletes (IHDP-CA) is suggested in this paper as a method that incorporates various aspects of positive psychology, mindfulness, resilience training, and the enhancement of interpersonal skills. Athletes at the College level can benefit from this allencompassing program’s emphasis on helping others, developing an attitude of gratitude, and meeting basic psychological requirements. Sports counseling services, schools, and College athletic teams can all benefit from the IHDP-CA. A more positive and supportive sporting environment can be achieved when the program takes a more holistic approach to athletes’ needs, improving their mental health, social connections, and overall performance. The possible effect of the IHDP-CA on the holistic development outcomes of College StudentAthletes will be predicted through simulation analysis. To gain a better understanding of the program’s long-term viability, efficacy, and scalability, this analysis will run simulations of different situations and tweak program settings.